Export Market Concentration, Earnings Stability, and International Finance Risk: Evidence from Indonesia’s Non Oil Exports - Eva Yuniarti Utami; Wahyu Agung Setyo; Nur Zarliani Uli; Sania Nuraziza; Novi Handayani Simbolon (Eastasouth Institute, 2026)
This study examines how export market concentration shapes export earnings stability from an international finance perspective. Using secondary data compiled from ITC Trade Map for Indonesia’s non oil exports during 2022-2025, the paper evaluates export value dynamics, destination market concentration, and the stability of foreign exchange generating export earnings. The analysis combines descriptive trend analysis, market share decomposition, the Herfindahl Hirschman Index (HHI), and the coefficient of variation (CV) of export earnings. The results indicate three main findings. First, Indonesia’s export earnings remained resilient despite global tightening, commodity price normalization, and exchange rate uncertainty. Second, export destinations were still moderately concentrated in a limited set of large markets, especially China, the United States, and India, implying exposure to partner specific demand shocks. Third, moderate diversification across secondary markets helped cushion aggregate earnings volatility, although sectoral dependence on a few commodities linked products remained visible. The study contributes to the international finance literature by showing that trade structure is not only a competitiveness issue but also a financial risk issue because export concentration affects foreign exchange inflows, external liquidity, and macro financial resilience. Policy implications include deeper market diversification, export upgrading, and broader use of trade finance and hedging instruments.